Usefulness of parent-completed ASQ for neurodevelopmental screening of preterm children at five years of age. - Marie Halbwachs (Public Library of Science (PLoS), 2013)
Introduction Preterm children are at greater risk of developmental impairment and require close follow-up for early and optimal medical care. Our goal was to examine use of the parent-completed Ages and Stages Questionnaire (ASQ) as a screening tool for neurodevelopmental disabilities in preterm infants at five years of age. Patients and methods A total of 648 preterm children (<35 weeks gestational age) born between 2003 and 2004 and included in the regional Loire Infant Follow-up network were evaluated at five years of age. ASQ was compared with two validated tools (Intelligence Quotient and Global School Adaptation Score) and the impact of maternal education on the accuracy of this questionnaire was assessed. Results Overall ASQ scores for predicting full-scale IQ<85 and GSA score produced an area under the receiver operating characteristic curve of 0.73±0.03 and 0.77±0.03, respectively. An ASQ cut-off value of 285 had optimal discriminatory power for identifying children with IQ scores<85 and GSA scores in the first quintile. ASQ values<285 were significantly associated with a higher risk of non-optimal neurologic outcomes (sensitivity of 0.80, specificity of 0.54 for IQ<85). ASQ values>285 were not distinctive for mild delay or normal development. In children with developmental delay, no difference was found when ASQ scores according to maternal education levels were analyzed. Conclusions ASQ at five years is a simple and cost-effective tool that can detect severe developmental delay in preterm children regardless of maternal education level, while its capacity to identify children with mild delay appears to be more limited.